Cryoprotective effect of cysteine on cryopreservation associated protein tyrosine phosphorylation in buffalo spermatozoa - MOHANARAO, G JAGAN; ATREJA, S K (The Indian Journal of Animal Sciences, 2013)
In the present study the effect of cysteine, an antioxidant, on cryopreservation associated cryodamage in the buffalo spermatozoa was studied. Ejaculated buffalo semen was divided into 2 aliquots. One aliquot was used to analyze fresh semen quality parameters and the other aliquot was cryopreserved in tris based egg-yolk extender with or without cysteine (5 mM) and sperm quality parameters like post-thaw motility, viability and membrane integrity were assessed. All the sperm quality parameters were significantly improved upon the addition of cysteine. Interestingly the number of tyrosine phosphorylated proteins detected was more (p32, p49, p55, p72, p86, p95 and p100) in cryopreserved sperm than the fresh spermatozoa. However the degree of protein tyrosine phosphorylation with respect to p49, p55, p72, p86, p95 and p100 proteins was significantly decreased in the cryopreserved spermatozoa supplemented with cysteine. Hence cysteine acts as a potential antioxidant that reduces the protein tyrosine phosphorylation probably caused by ROS induced signaling pathways by maintaining other sperm quality parameters. The addition of cysteine to the freezing extender helps in minimizing the cryodamage associated with sperm cryopreservation.